2021
DOI: 10.2147/nss.s323160
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of Sleep as a Specific Risk Factor for Poor Metabolic and Mental Health: A UK Biobank Study of 84,404 Participants

Abstract: Purpose Short and long sleep durations have adverse effects on physical and mental health. However, most studies are based on self-reported sleep duration and health status. Therefore, this longitudinal study aims to investigate objectively measured sleep duration and subsequent primary health care records in older adults to investigate the impact of sleep duration and fragmentation on physical and mental health. Methods Data on objective sleep duration were measured us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 55 publications
0
18
0
Order By: Relevance
“…When investigating movement behaviors, it is important to note that the length of the day is limited to 24 h, suggesting an increases in the time spent in one behavior must result in a decrease in the time spent in associated behaviors. There is potent evidence for sedentary behaviors [ 31 , 32 ], sleep [ 33 , 34 , 35 ], and MVPA [ 36 , 37 , 38 ], and emerging evidence for LPA to be associated with health outcomes [ 39 , 40 ]. Moreover, the allocation of whole 24 h time is associated with health outcomes across the lifespan [ 41 , 42 , 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…When investigating movement behaviors, it is important to note that the length of the day is limited to 24 h, suggesting an increases in the time spent in one behavior must result in a decrease in the time spent in associated behaviors. There is potent evidence for sedentary behaviors [ 31 , 32 ], sleep [ 33 , 34 , 35 ], and MVPA [ 36 , 37 , 38 ], and emerging evidence for LPA to be associated with health outcomes [ 39 , 40 ]. Moreover, the allocation of whole 24 h time is associated with health outcomes across the lifespan [ 41 , 42 , 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Sleep is essential for life and plays key roles for optimal physiology, brain functioning, and health. [3][4][5][6] Cerebral white matter is composed of myelinated axons that connect neurons in different brain regions into functional circuits. Myelin is formed by oligodendrocytes and acts as an insulator, which allows high-speed electrical impulse transmission.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have demonstrated a relationship between short sleep duration and increased risks of obesity [ 9 , 10 , 11 ]. Obesity is one of the largest public health crises facing American society, and it is a serious condition that has an established role in predisposing individuals to several chronic diseases.…”
Section: Inadequate Sleep Health and Obesitymentioning
confidence: 99%
“…This is important because inflammation is the basis of many diseases, as we will see in the coming sections. Sleep loss has been shown to lead to higher levels of inflammatory signaling, specifically through cytokines like TNFα, IL-6, and C reactive protein (CRP) [ 11 , 105 , 106 ]. It is thought that IL-6 might play a role in sleep regulation, based on a study that found that sleep deprivation changed the pattern of IL-6 secretion causing daytime oversecretion and nighttime undersecretion [ 107 ].…”
Section: Sleep Health and Immunity: Inflammationmentioning
confidence: 99%